Stephen M. Park. The Pan American Imagination: Contested Visions of the Hemisphere in Twentieth-Century Literature. Charlottesville and London: U of Virginia P, 2014. 269 pp. - Maria José Somerlate Barbosa (Studies in 20th & 21st Century Literature, 2017)
Review of Stephen M. Park. The Pan American Imagination: Contested Visions of the Hemisphere in Twentieth-Century Literature. Charlottesville and London: U of Virginia P, 2014. 269 pp.
Keywords: Pan American Imagination